New Graphical User Interface for EXAFS analysis with the GNXAS suite of programs. (May 2016) - Hatada, Keisuke; Iesari, Fabio; Properzi, Leonardo; Minicucci, M.; Cicco, Andrea di
Abstract: GNXAS is a suite of programs based on multiple scattering calculations which performs a structural refinement of EXAFS spectra. It can be used for any system although it has been mainly developed to determine the local structure of disordered substances. We developed a user-friendly graphical user interface (GUI) to facilitate use of the codes by using wxPython. The developed GUI and the codes are multiplatform running on Windows, Macintosh and Linux systems, and are free shareware (http://gnxas.unicam.it ). In this work we illustrate features and potentials of this newly developed version of GNXAS ( w -GNXAS).